EVALUASI PELAKSANAAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SD NEGERI KARANGDUREN 02 - Koko Wijayanto; Adi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the context, input, process, and product of the implementation of the Strengthening the Profile of Pancasila Students (P5) program at SD Negeri Karangduren 02. Conducted comprehensively using the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam, this research is an evaluative study with a descriptive qualitative approach. Data were collected through in-depth interviews, document studies, and a Likert scale questionnaire as supporting evidence. The research subjects were the principal, 2 teachers (from upper and lower grades), and 4 students (2 from upper and 2 lower grades), selected using a purposive sampling technique. The results indicate that: (1) The context aspect was in the "Very Good" category (100%). The P5 program has a strong policy foundation, aligns with the school's vision and mission, and the "Sustainable Lifestyle" theme is relevant to students' needs. (2) The input aspect was in the "Very Good" category (89.7%). Teacher readiness and learning modules were excellent, although there were some limitations in supporting facilities and infrastructure. (3) The process aspect was in the "Very Good" category (94.4%). The implementation of P5 was effective and collaborative, supported by the teachers' role as facilitators and the principal's regular monitoring. (4) The product aspect was in the "Very Good" category (88.8%). The P5 program successfully fostered the dimensions of the Pancasila Student Profile in students, as shown by positive behavioral changes such as independence, cooperation, and responsibility, as well as evidence of student work. Overall, the implementation of P5 at SD Negeri Karangduren 02 has been highly effective in shaping student character. The recommendation proposed is to improve facilities and infrastructure to further optimize students' learning experiences.